The decision to return in times of crisis. A comparative perspective on Ecuadorian and Romanian migrants in Spain - López de Lera, Diego; Pérez-Caramés, Antía (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2015)
This article will address the decision-making processes regarding return migration made by immigrants in Spain within the context of current crisis that, as we will analyse, has led, in many cases, to a decline in migrants’ employment rates and the loss of administrative regularity. The phenomenon of return migration will be analysed within the broader change in the migratory cycle that is living in Spain through demographic analysis of the recent history of migration flows. The process of decision-making, as well as the design of strategies, will be studied, comparing particularly two of the largest migratory communities in Spain: Ecuadorians and Romanians. We will outline the main elements taken intoconsideration when deciding taking the way back home.
Keywords: return migration; Romanian migration; Ecuadorian migration; migratory strategies; decision-making